2021
DOI: 10.3390/ani11092575
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Animal Welfare and Antimicrobial Use in Italian Dairy Farms

Abstract: Information regarding the relationship between animal welfare (AW) and antimicrobial use (AMU) in dairy cows is limited. The current study aimed to investigate this relationship on Italian farms and to identify potential targets of AMU reduction. The study was performed at 79 Italian dairy farms housing over 15,000 cows during 2019. AW was scored with an on-farm protocol assessing farm management and staff training, housing systems, and animal-based measures. AMU was estimated using a defined daily dose per kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 41 publications
(55 reference statements)
3
14
0
Order By: Relevance
“…Our results support this evidence, as we traced a positive correlation between milk production and AMU. In line with what is reported in the literature for dairy cattle [ 27 , 30 , 32 , 34 ], we found that intramammary medication is the most frequent administration route (53.11%). Previous studies observed a frequency reaching 63% [ 32 ] and 78% [ 34 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results support this evidence, as we traced a positive correlation between milk production and AMU. In line with what is reported in the literature for dairy cattle [ 27 , 30 , 32 , 34 ], we found that intramammary medication is the most frequent administration route (53.11%). Previous studies observed a frequency reaching 63% [ 32 ] and 78% [ 34 ].…”
Section: Discussionsupporting
confidence: 92%
“…Considering a three-year timeframe can overcome outlier peak values due to exceptional circumstances and evidenced a significant decreasing trend. A previous Italian study [ 30 ] assessed AMU in dairy cattle farms using DDDAit in 2019 in north-western Italy (Lombardy region). These authors observed a similar AMU compared to the present study (4.8 DDDAit per cow/year).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The protocols were developed by the Italian National Reference Centre for Animal Welfare (CReNBA), Istituto Zooprofilattico Sperimentale della Lombardia e dell’Emilia Romagna (IZSLER). They are currently posted on the ClassyFarm platform of the Italian Ministry of Health for monitoring and benchmarking animal welfare on farms [ 25 , 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…The welfare assessment protocol for tie-stall farms lists 58 indicators, while the protocol for free-stall farms lists 70 indicators. The indicators are grouped by section: Section A—farm management and staff training, Section B—housing and equipment, and Section C—animal-based measures (ABMs) [ 25 ]. Each indicator has two or three well-defined risk levels: level 1 indicates a high risk or poor status of the indicator, level 2 indicates a medium risk, and level 3 indicates a low risk or better status of the indicator [ 27 , 28 ].…”
Section: Methodsmentioning
confidence: 99%